TRAINING MOTIVATION: A PREDICTOR OF TRANSFER TRAINING IN THE MALAYSIAN ARMY INFANTRY CORPS LEADERSHIP DEVELOPMENT PROGRAM - Noor Azmi Mohd Zainol; Zahimi Zainol Abidin; Mohammad Daud Johari; Daud Mohamed Salleh; Khairul Nizam Taib, (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
Military leaders strive to achieve their organization's vision and mission in accordance with their duties, authorities, and responsibilities. The challenging climate in military units due to misconduct, lack of discipline, and ineffective leadership has highlighted the need for more effective leadership development activities. Therefore, the purpose of this study is to measure the influence of training motivation in the relationship between leadership development programs and training transfer. A total of 412 completed questionnaires filled out by respondents serving in the Malaysian Army Infantry Corps were analyzed using the SmartPLS 3.3.9 software package. The findings of the factor validation analysis show that the measurement scale of this study has reached the standard level of validity and reliability analysis. Further, the results of hypothesis testing using the SmartPLS path model highlight two important findings: first, the relationship between course content and training motivation has a positive and significant relationship with training transfer. Second, the relationship between training methods and training motivation has a positive and significant relationship with training transfer. Based on a statistical perspective, the findings of this study confirm that training motivation acts as an intervening variable between the leadership development program and the transfer of training in the study organization. Therefore, discussion, research implications and conclusions are also given attention in this study.